A Study of Learning Achievement on Ecosystem Adventure Worldwide Learning Unit and Scientific Mind of the Grade 9 Students Using Science, Technology, Society and Environment Approach (STSE) - Wiangsuk, Panuwat; Keeratichamroen, Wasana (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The Science, Technology, Society, and Environment Approach (STSE) is important in encouraging students to able to learn including integrating learning about science into daily life environment and it will lead to presenting the way to fix the problem by connecting between science, technology, society, and environment. The purposes of this study were to 1) compare grade 9 students learning achievement before and after learning using Science, Technology, Society and Environment Approach, 2) compare grade 9 students’ learning achievement after learning using Science, Technology, Society and Environment Approach with a criterion of 70 percent, and 3) compare the scientific mind of grade 9 students before and after learning using Science, Technology, Society and Environment Approach. Methodology: The sample group of this study was 18 grade 9 students in the second academic year of 2023 at Phupra Witthayokhom School. The sample was selected using cluster random sampling. The research instruments were lesson plans based on the Science, Technology, Society, and Environment Approach, achievement tests and Scientific Mind questionnaires. The data were statistically analyzed by percentage, mean, Standard Deviation, t-test, and Kolmogorov-Smirnov test. Results: The findings of this research were as follows: 1) Learning achievement of grade 9 students after using the Science, Technology, Society, and Environment Approach was significantly higher than before learning at the .05 level. 2) The learning achievement of grade 9 students after using the Science, Technology, Society and Environment Approach was not significantly higher than the 70% criterion at the .05 level. and 3) The Scientific mind of grade 9 students after using the Science, Technology, Society, and Environment Approach was significantly higher than before learning including overall and each part at the .05 level. Conclusion: The study reveals that the implementation of a learning approach based on the principles of science, technology, society, and environment significantly enhances the academic performance of third-year high school students. A statistically significant increase in learning outcomes is observed in various subjects, including adventure learning related to environmental systems. Overall, the findings underscore the positive impact of incorporating scientific, technological, social, and environmental perspectives into the curriculum, contributing to improved academic achievements among third-year high school students.